Control de inventario en bodega de la empresa constructora Arregui Dávila s.a. del cantón Babahoyo. - Zajia Bravo, Daniela Alejandra (2022)
Inventory controls help the company to have updated information and avoid unnecessary loss of its products, as well as to have a complex stock of what is required. In this case study "INVENTORY CONTROL IN THE WAREHOUSE OF THE CONSTRUCTION COMPANY ARREGUI DÁVILA S.A. IN BABAHOYO CANTON", it was possible to notice one of the most serious problems such as the lack of an updated and automated system, the little knowledge that the person in charge of the warehouse department of the company has on these issues, since the information is regularly handled manually, so the main objective was to identify the incidence of inventory control in these warehouses. For which a qualitative methodology was used, focused on a descriptive study, applying the deductive method that allowed through the interview technique to know about the reality of the warehouse of the construction company Arregui Dávila S.A. in issues related to inventory control. The conclusion was that it is urgent to have an updated and automated system, in the same way that the person in charge of this space is highly trained to avoid serious future problems to the company.